The creative loop how the brain makes a mind - Harth, Erich (Addison-Wesley Publishing Company, 1993)
"Where is the seat of consciousness within the brain? How can we account for a continuum that begins with cells and neurochemicals and ends with such ethereal qualities as imagination, creativity, and that elusive being we call the "self"?" "In The Creative Loop, Erich Harth, a distinguished researcher in the physics of perception, offers a persuasive theory that explains in detailed fashion how the brain creates the conscious self, the "I" that we all experience as separate from the "It" of the rest of the world." "The split known as the "mind-body problem" is, of course, one of the oldest questions of science and philosophy and is still among the most hotly debated today. The classical view held that there was some sort of spirit or homunculus hovering above the physical brain, looking down on the central stage of our perceptions. The prevailing scientific view today rejects not only spirit but also the very hope of there being any "central meaner" observing and making sense of experience, preferring to see unified consciousness itself as a delusion. Whereas Marvin Minsky offers us The Society of Mind and the philosopher Daniel Dennett even describes "an army of idiots" within our brains, Harth presents a view, based on long-known but generally overlooked features of brain structure, that flies in the face of orthodox materialism.". "Harth takes us out of the old Newtonian world of machine models of the brain and into the almost mystical realm of contemporary physics, focusing on specific structures - the relays within the sensory pathways linking the sense organs and the cerebral cortex - that send information back and forth. It is these relays that, in Harth's view, ultimately give rise to consciousness and creativity. Each relay serves as a "sketch pad" where perceptions are received and modified before being passed along. Thus what reaches the cortex is not the unvarnished truth but a truth filtered and personalized through improvisation, much like a child talking to herself as she practices her language ability. There is, then, in Harth's view, a unified consciousness built up within the biology of the brain. It simply does not reside atop the system, but rather is deeply embedded within this "hall of mirrors" at the bottom." "Unlike the orthodox view which finds no place for freedom of the will in its description of the brain, Harth's approach is a celebration of the messy, intuitive nature of human consciousness and the creativity it exhibits. The beauty of this theory, and of this often lyrical book, lies in its reconciliation of the cold facts of biology and physics with our most humanistic aspirations."